PARADIGMA KEBEBASAN BERPENDAPAT: ANONIMITAS, BUDAYA PARTISIPASI, DAN DOMINASI SUBYEKTIFITAS PENGETAHUAN DI RUANG DIGITAL - Wardhana, Arya Wijaya Pramodha; Tiara, Ayunda Trisna Ludi; Sugihartati, Rahma; Asmiyanto, Taufik; Wibowo, Muhamad Prabu (Universitas Mataram, 2024)
Social networking is a platform where various users with different information needs, and access purposes come together. With this condition, to ensure the security and privacy comfort of users, Anonymity has emerged as a